Contact application of Lamiaceae botanicals reduces bean weevil infestation in stored beans - Jevremović, Stojan; Lazarević, Jelica; Kostić, Miroslav; Krnjajić, Slobodan; Ugrenović, Vladan; Radonjić, Anđa; Kostić, Igor (Archives of Biological Sciences, 2019)
Paper description: Thyme, rosemary and basil essential oils (EOs) and their dominant components (DCs) are known to have fumigant toxic properties against stored insects. We tested the contact insecticidal and anti-oviposition effects of these EOs and their DCs against bean weevil (BW). Thyme EO and thymol exhibited strong residual contact toxicity against BW; thyme EO, thymol and α-pinene, deterred oviposition and all tested botanicals reduced oviposition in BW females. Thyme EO and thymol possess the potential to be used as bioinsecticides for sustainable control of BW in storage. Abstract: The bean weevil (Acanthoscelides obtectus, Say) is a serious pest of stored bean seeds. Bean weevil control relies heavily on the use of synthetic insecticides. In the search for a sustainable alternative, the residual contact toxicity and anti-oviposition activity of thyme (Thymus vulgaris L.), rosemary (Rosmarinus officinalis L.) and basil (Ocimum basilicum L.) essential oils as well as their dominant components (thymol, α-pinene, 1,8-cineole and linalool) were tested against A. obtectus adults. Out of the seven tested botanicals, T. vulgaris oil, thymol and linalool exhibited the highest toxic potential (>90% mortality). Females were less susceptible than males. The insecticidal activity of these botanicals was much greater when they were applied on glass compared to direct application to the bean. All tested botanicals reduced oviposition by bean weevil females. T. vulgaris oil, thymol and α-pinene also deterred bean weevil oviposition, as revealed by a two-choice test. Our research shows that T. vulgaris oil and thymol are promising and sustainable alternatives to synthetic pesticides for protecting stored beans against the bean weevil. https://doi.org/10.2298/ABS190617049J Received: June 17, 2019; Revised: July 17, 2019; Accepted: August 14, 2019; Published online: August 30, 2019 How to cite this article: Jevremović S, Lazarević J, Kostić M, Krnjajić S, Ugrenović V, Radonjić A, Kostić I. Contact application of lamiaceae botanicals reduces bean weevil infestation in stored beans. Arch Biol Sci. 2019;71(4):665-76.